2020
DOI: 10.3390/s21010143
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-Short Baseline Underwater Positioning System with Kalman Filtering

Abstract: The ultra-short baseline underwater positioning is one of the most widely applied methods in underwater positioning and navigation due to its simplicity, efficiency, low cost, and accuracy. However, there exists environmental noise, which has negative impacts on the positioning accuracy during the ultra-short baseline (USBL) positioning process, which results in a large positioning error. The positioning result may lead to wrong decision-making in the latter processing. So, it is necessary to consider the erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…For a standalone SINS, its positioning error accumulates over time; nevertheless, the high-precision positioning technology needs the application of statistical methods for isolation of nonproperly operating sensors [22]. In the work [23], it is shown that the high-precision phase difference information can be obtained based on the non-equidistant quaternary array and the phase difference acquisition mechanism.…”
Section: Ultra-short Baseline Systemsmentioning
confidence: 99%
“…For a standalone SINS, its positioning error accumulates over time; nevertheless, the high-precision positioning technology needs the application of statistical methods for isolation of nonproperly operating sensors [22]. In the work [23], it is shown that the high-precision phase difference information can be obtained based on the non-equidistant quaternary array and the phase difference acquisition mechanism.…”
Section: Ultra-short Baseline Systemsmentioning
confidence: 99%
“…The second new array is shown in Figure 3. According to formula (6), under the influence of noise when 12 14 13 2 cos…”
Section: Three Arrays and Algorithm Principlementioning
confidence: 99%
“…Zheng Enming [10] optimized the traditional array elements, basically using small spacing array elements to solve ambiguity and large spacing array elements to improve positioning accuracy. Luo Qinghua [11,12] introduced Kalman filter-based methodology on the array designed by Zheng Enming to improve the positioning accuracy, but these improvements do not improve the poor localization performance of signals at a large incident angle. Liang Guolong [13] proposed using depth information to assist localization to improve the positioning accuracy by up to 0.25%.…”
Section: Introductionmentioning
confidence: 99%
“…And this can not satisfy the increasing needs from applications [5][6]. Since there are many different kinds of navigation and positioning subsystems that have specific characteristics respectively [7], such as SINS, DVL, visual navigation, and USBL [8], we can integrate these subsystems to enhance the overall accuracy and the robustness of the positioning method. Through an integrated approach, we can get higher accuracy and stability of the navigation and positioning system in a long time by performing information fusion and filter correction.…”
Section: Introductionmentioning
confidence: 99%